Probability analysis of undrained clay slope stability considering strength anisotropy and heterogeneous rotated anisotropy - Cao, Wei; Li, Wenjing; Yi, Haiyang; Liu, Yuanyuan (Frontiers in Earth Science, 2025)
Strength anisotropy and heterogeneous rotated anisotropy are prevalent phenomena in natural slopes. Previous studies have underscored their significance in slope stability analysis. However, in previous slope stability analyses, the effects of strength anisotropy and heterogeneous rotated anisotropy on slope stability were studied separately, without considering their coupled effect. This paper aims to propose a probabilistic analysis framework of slope stability considering the coupled effect of strength anisotropy and heterogeneous rotated anisotropy. Through an undrained clay slope case, the proposed probabilistic analysis framework is examined. The influence of strength anisotropy and heterogeneous rotated anisotropy on slope stability is investigated. The results show that the proposed probabilistic analysis framework of slope stability considering the coupled effect of strength anisotropy and heterogeneous rotated anisotropy is effective. Both strength anisotropy and heterogeneous rotated anisotropy have an important influence on slope stability. Furthermore, the statistics of safety factor including mean value, coefficient of variation, and reliability index, vary with the strength anisotropy coefficient, the heterogeneous anisotropy coefficient, and the rotational angle. The smaller the strength anisotropy coefficient, the larger the heterogeneous anisotropy coefficient, and the smaller the reliability index. The rotational angle of strata corresponding to the minimum and maximum values of the slope reliability index is sensitive to the strength anisotropy coefficient, but not to the heterogeneous anisotropy coefficient.